DRAINAGE ANALYSIS OF JAKARTA BANDUNG HIGH SPEED TRAIN STATION AT HALIM STATION USING HEC-RASS - Imamuddin, Mohammad; Mahmuda, Diva Quinta (International Journal of Civil Engineering and Infrastructure, 2024)
Halim Station is the main station in the Jakarta-Bandung High-Speed Train project, playing a crucial role in facilitating travel between the two metropolitan cities. The Halim Station building for the Jakarta-Bandung High-Speed Train is located on the Jakarta - Cikampek Toll Road at KM 0+800, East Jakarta City. Halim Station is the first station for departure and the last stop for journeys using the Jakarta-Bandung High-Speed Train. The area of the Halim Station building is 25,700 m2 with a roof area of 31,100 m2. Each day, the water source to meet operational needs at Halim Station comes from the Regional Water Company (PDAM) with a maximum daily clean water usage limit of 210 m3. The utilization of rainwater in the context of high-speed train stations has significant potential to meet operational sanitation and water needs around the station. With proper rainwater collection, storage, and management systems, rainwater can be processed into a safe and quality water source for various purposes around the station. If there is excess rainwater not needed for the building's operational requirements, the calculation will also include the need for infiltration wells and drainage channels. The utilization of rainwater as an alternative water source for operational needs is expected to completely replace the water source of Halim Station, which previously came from PDAM. Therefore, this could contribute to efforts to reduce environmental impacts and conserve water resources in Indonesia.